ADJUNCTIVE PYRIDOXINE FOR SEVERE TETANUS : A CASE REPORT WITH LITERATURE REVIEW - Handayani, Fitriah; Kaelan, Cahyono (Medika Tadulako: Jurnal Ilmiah Kedokteran Fakultas Kedokteran dan Ilmu Kesehatan, 2016)
Introduction : Tetanus is an acute, potentially fatal infectious disease that is characterized by seizure (general motor spasm), lockjaw, opisthotonus, defans muscular, rhisus sardonicus. A high mortality case remains tetanus need special attention. Pyridoxine 100mg orally introduced as adjunctive therapy for spasm, aimed to reduce mortality rate.Case report : A 38-years-old man with lockjaw (< 1cm) accompanied by severe seizures (general motor spasm) that arise many-times caused the patient body arched back (opisthotonus), rhisus sardonices and defans muscular categorized severe tetanus (5 points of Dakar score). Based neuroinfection study grup of Indonesian Neurologist, tetanus patient treated with Human Tetanus Immune Globulin (HTIG) to neutralized toxins, antibiotics penicillin and metronidazole to eradicated causative bacterial, and diazepam (benzodiazepine) to handle seizures (general motor spasm). Pyridoxine (vitamin B6) 100mg used as adjuntive therapy for treated seizure aimed to reduce mortality risk. Patient hospitalized for 18 days and discharged with good condition (free spasm).Conclusion : The role of pyridoxine in the management tetanus may sinergism with diazepam for reduced general motor spasm (seizures), but it should be re-examined in a blind randomised trial.Â Key word : tetanus, seizures (general motor spasm), lockjaw, pyridoxine, diazepam.